107k views
2 votes
Can someone please do this substitution method question with the working out.

T = 1/2m^2+2m-4
T = 2m+4

1 Answer

4 votes

Answer:

Explanation:


T = (1)/(2)m^(2)+2m - 4\\\\T = 2m + 4\\\\(1)/(2)m^(2)+2m - 4 = 2m + 4\\\\(1)/(2)m^(2)+2m - 4 - 2m - 4 = 0

Combine like terms


(1)/(2)m^(2)+2m - 2m - 4 - 4 = 0\\\\(1)/(2)m^(2) - 8 = 0\\\\(1)/(2)m^(2) =8\\\\m^(2) = 8*2\\\\m^(2) = 16\\\\m = √(16)

m = ± 4

User Tayyab Vohra
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.